2003
DOI: 10.1088/0960-1317/14/2/016
|View full text |Cite
|
Sign up to set email alerts
|

Micro-ball lens array modeling and fabrication using thermal reflow in two polymer layers

Abstract: This paper presents a mathematical model to design and fabricate micro-ball lens array using thermal reflow in two polymer layers. The experimental results showed that micro-ball lens arrays were fabricated and integrated onto a planar substrate. Two polymer layers were coated onto a silicon substrate. The upper layer was a photoresist. The lower layer was a polyimide material. The polyimide was expected to form a pedestal to sustain the ball lens after the heat reflow process. Once the patterned polymer is he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Better improvement could be made if more complicated fabrication process was applied. For example, truly 3-D microlens structures could be made using more complex and expensive process [20,21]. Nevertheless, the easy and cheap fabrication process described in the study is sufficient to fabricate a disposable CE chip for bioanalytical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Better improvement could be made if more complicated fabrication process was applied. For example, truly 3-D microlens structures could be made using more complex and expensive process [20,21]. Nevertheless, the easy and cheap fabrication process described in the study is sufficient to fabricate a disposable CE chip for bioanalytical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Real-time in-situ characterization and control of the nanostructures during their formation, by which an ordered array of nanoscale LEDs or a shaped light emitting region with submicrometer precision can be produced, were presented [5]. In addition, many special processes based on semiconductor process were also developed for fabricating microstructures such as backside 3D diffuser lithography [6], optical lithography using a high energy beam sensitive glass gray-level mask [7], ink-jet printing [8], thermal reflow in two polymer layers [9], soft molding [10], fabrication of various dimensions of high fill-factor micro-lens arrays for OLED (Organic Light Emitting Diode) package [11] and multi-step X-ray exposures to fabricate microstructure [12]. However, backside 3D diffuser lithography and glass gray-level mask methods increase the cost of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hsiharng et al reported a mushroom-shaped micro-lens using a double-layered polymer [13,14]. This seems to match the wafer-level packaging of edge-emitting devices.…”
Section: Introductionmentioning
confidence: 99%